Properties of solutions of a mixed problem for a nonlinear ultraparabolic equation - Protsakh, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
Mixed problems for a nonlinear ultraparabolic equation are considered in domains bounded and unbounded with respect to the space variables. Conditions for the existence and uniqueness of solutions of these problems are established and some estimates for these solutions are obtained.